Tropospheric Scintillation with Rain Attenuation of Ku Band at Tropical Region - Ibtihal F El-shami; Lam Hong Yin; Jafri Din; Ali l Elgayar; Manhal Alhilali (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
Tropospheric scintillation can become a significant impairment in satellite communication systems, especially in tropical regions with frequencies higher than 10 GHz, the attenuation is dramatically affecting the scintillation. This work concentrates on those aspects in equatorial Johor Bahru, Malaysia, based on a one-year Ku-band propagation measurement campaign, utilizing the equipment of Direct Broadcast Receiver (DBR) and Automatic Weather Station (AWS). This study investigates the relationship between wet scintillation and rain attenuation using experimental measurement and concentrate on the probability density function (PDF) of different scintillation parameters. From the results, it is concluded that wet scintillation intensity increases with rain attenuation. Thus, the relationship can be phrased by linear equations or power-law. The PDFs of wet scintillation intensity, adapted to a given rain attenuation level, are found lognormally distributed, leading to selection of method for determining the relation between conditional PDFs and rain attenuation.